BREAST CANCER CHEMOTHERAPY RESPONSE IN WAHIDIN SUDIROHUSODO HOSPITAL, MAKASSAR - Prihantono, Prihantono; Haryasena, Haryasena; Sampepajung, Daniel (Nusantara Medical Science Journal, 2016)
ABSTRACT Introduction: Treatments of breast cancer are multidisciplinary. Chemotherapy is one of the most important modalities and has become the standard of breast cancer treatment of in the adjuvant or neoadjuvant setting. Evaluation is needed in order to understand the effectivity of the chemotherapy regiment, to improve the service system and to share with other centers. Objectives: to understand the characteristics of chemotherapy patients, types of regimen, settings chemotherapy and neoadjuvant chemotherapy response of breast cancer. Methods: A retrospective study was done by reviewing the administrative data of cancer patients who were treated in the surgical oncology Wahidin Sudirohusodo Hospital, Makassar in 2014. Results: During 2014 has been carried out chemotherapy for 247 breast cancer patients, used as neoadjuvan setting 145 cases (59 %) and Adjuvan 102 cases (41%). The regimen used are CAF 155 cases ( 63%), TAC 55 cases ( 22 %), TA 20 cases (8%), GC 11 cases ( 5%), dan Vinoralbine 6 cases (2%). Cumulative Clinical Response are: complete response 3 cases (2%), partial response 112 cases (78%), stable disease 23 cases (15%), and progresive disease 9 (5%). Chemoterapy response by subtype: Luminal 67%, Her2 70%, Triple Negatif 88%. Conclusions: Breast cancer clinical response to various chemotherapy regimens are good, regimen and subtype affect the response to chemotherapy. Keywords: breast cancer, chemotherapy, clinical response